Analysis of combining ability in soybean cultivars - Gavioli, Eduardo Antonio; Perecin, Dilermando [UNESP]; Di Mauro, Antonio Orlando [UNESP] (Byte Systems - Solucoes Digitais, 2006)
Eight soybean cultivars (Doko, Bossier, Ocepar-4, BR-15, FT-Cometa, Savana, Paraná and Cristalina) were crossed in a diallel design. Plants of the F1 generation and their parents were evaluated under short-day conditions for the determination of the general (GCA) and specific (SCA) combining ability. The estimated GCA and SCA values were significant for the evaluated traits except for the total cycle. Highest GCA effects for the traits days to flowering, plant height, insertion height, number of branches and total cycle were estimated for the cultivars Doko, Cristalina and Savana. The variability observed in the trait days to flowering can, for the most part, be explained by additive effects.
Keywords: Diallel; Flowering; Glycine max; Heterosis; Magnoliophyta